Impact of ixazomib‐lenalidomide‐dexamethasone therapy on overall survival in multiple myeloma patients: Analysis of the emerging‐markets subgroup of the TOURMALINE‐MM1 trial - Andrew Spencer; Olga Samoilova; Wee‐Joo Chng; Richard Labotka; Cong Li; Kwang‐Wei Wu; Nakul Saxena; Xu Yan; Jae Hoon Lee; Meral Beksac (eJHaem, 2022)
Abstract Ixazomib‐lenalidomide‐dexamethasone (ixazomib‐Rd) showed clinical efficacy over placebo‐Rd in patients with relapsed/refractory multiple myeloma (MM) in the TOURMALINE‐MM1 trial. Over a median follow‐up of ∼85 months, as patients showed disease progression, they received subsequent novel therapies that confounded the overall survival (OS) benefit. Here, we conducted a post hoc analysis in 148 patients from seven countries defined as emerging markets, with limited access to novel therapies for MM during the trial period, to describe the impact of these therapies on OS. Patients were randomised to ixazomib‐Rd (n = 71) or placebo‐Rd (n = 77). The median progression‐free survival (PFS) was 18.7 versus 10.2 months, with ixazomib‐Rd versus placebo‐Rd (hazard ratio [HR], 0.504; p = 0.008) demonstrating a statistically significant improvement as observed in the primary trial. The median OS improved by 32.6 months with ixazomib‐Rd over placebo‐Rd (63.5 vs. 30.9 months; HR, 0.794; p = 0.261); however, the statistically significant benefit seen in PFS was not observed for OS. Improvement with ixazomib‐Rd over placebo‐Rd was observed in overall response (81.7% vs. 64.9%; odds ratio [OR], 2.38; p = 0.019) and complete response (22.5% vs. 3.9%; OR, 7.57; p < 0.001). Patient‐reported quality of life and use of subsequent therapies were similar across treatment groups. No new safety concerns were identified. Compared with the main cohort, median OS was 10 months longer with ixazomib‐Rd and 21 months shorter with placebo‐Rd in this subgroup, indicating a clinically meaningful survival benefit of ixazomib‐Rd treatment in this patient population with limited access to subsequent novel therapies.